Role of Usability on using Biometrics for Cybersecurity - Hausawi, Yasser (Discoveries in Agriculture and Food Sciences, 2019)
ABSTRACT Biometrics are traits that allow individuals to be identified. Popular biometrics include fingerprints, faces, and irides. A common use of biometric systems is for authentication of users desiring access to a system or resource. However, the use of biometrics presents challenges and opportunities unique to other authentication methods, such as passwords and tokens. Biometric systems are also vulnerable to poor usability. Such systems must be engineered with wide user accessibility and acceptability in mind, but must still provide robust security as well. As lack of usability causes systems’ failures, and enhancing systems’ usability reduces such failures. This article first presents an overview of biometric systems employed today, including their usage and security merits. We then consider the specific role usability plays on both the development and long-term utility of biometric systems used for Cybersecurity.